2011
DOI: 10.1016/j.joep.2010.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Life Satisfaction and Child Outcomes: Are They Related?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…54 Clark et al (2008) find that it is not absolute but relative income which matters for happiness, because individuals compare their income both to others (social comparison) and to themselves in the past (habituation). Berger and Spiess (2011) investigate the relationship between maternal life satisfaction and child outcomes using data from the GSOEP. They find that higher maternal life satisfaction leads to better socio-economic development at the age of 5 to 6 years.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…54 Clark et al (2008) find that it is not absolute but relative income which matters for happiness, because individuals compare their income both to others (social comparison) and to themselves in the past (habituation). Berger and Spiess (2011) investigate the relationship between maternal life satisfaction and child outcomes using data from the GSOEP. They find that higher maternal life satisfaction leads to better socio-economic development at the age of 5 to 6 years.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…According to RWI (2008), most parents were not aware of the progressivity effect when receiving Elterngeld and thus even overestimated the gain in income. Berger and Spiess (2011) showed that the verbal skills of 2-3-year-olds improve the higher their mother's life satisfaction is. This can be explained by either qualitatively better attachment or better parenting behavior of happy mothers.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal job loss might decrease a mother's life satisfaction which in turn could deteriorate the emotional stability of her relationship with her child, since a mother might have re-entered the labor market after being dissatisfied with "solely" being a mother (see for example the study on maternal life satisfaction and child outcomes by Berger & Spiess 2011). A change in parents' emotional balance is closely related to the literature on unemployment and life satisfaction (see for example the work by Clark et al (2010) or Knabe et al (2010)).…”
Section: Related Literaturementioning
confidence: 99%
“…The SOEP started in 1984 and is an annual household panel 8 that comprises a series of mother-child questionnaires as well as a youth specific questionnaire. The child-specific modules of the SOEP 7 Berger & Spiess (2011) show that higher maternal life satisfaction decreases children's socio-emotional problems. They argue that the positive effect of maternal life satisfaction stems from more responsiveness to the children, which affects the quality of mother-child interactions.…”
Section: Datamentioning
confidence: 99%